Options to reform the European Union legislation on GMOs - risk governance - Eriksson, Dennis; Custers, Rene; Bjornberg, Karin Edvardsson; Hansson, Sven Ove; Purnhagen, Kai; Qaim, Matin; Romeis, Jorg; Schiemann, Joachim; Schleissing, Stephan; Tosun, Jale; Visser, Richard G. F. (Trends in biotechnology, 2020)
Here, we discuss options to reform the EU genetically modified organism (GMO) regulatory framework, to make risk assessment and decision-making more consistent with scientific principles, and to lay the groundwork for international coherence. We discussed the scope and definitions in a previous article and, thus, here we focus on the procedures for risk assessment and risk management.